2011
DOI: 10.1016/j.yexcr.2011.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of matrix metalloproteinase-9 activity by doxycycline ameliorates RANK ligand-induced osteoclast differentiation in vitro and in vivo

Abstract: Tetracycline antibiotics, including Doxycycline (DOX), have been used to treat bone resorptive diseases, partially because of their activity to suppress osteoclastogenesis induced by receptor activator of nuclear factor kappa B ligand (RANKL). However, their precise inhibitory mechanism remains unclear. Therefore, the present study examined the effect of Dox on osteoclastogenesis signaling induced by RANKL, both in vitro and in vivo. Although Dox inhibited RANKL-induced osteoclastogenesis and down-modulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 40 publications
7
44
0
3
Order By: Relevance
“…A reduction in MMP-9 activity may limit bone resorption associated with arthritis by decreasing RANKL expression. This association is based on the results of other investigators showing that MMP-9 can induce RANKL activity, and a reduction in MMP-9 can reduce RANKL [35]. Thus, Pristimerin might block this bi-directional cross-talk resulting in protection against bone damage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A reduction in MMP-9 activity may limit bone resorption associated with arthritis by decreasing RANKL expression. This association is based on the results of other investigators showing that MMP-9 can induce RANKL activity, and a reduction in MMP-9 can reduce RANKL [35]. Thus, Pristimerin might block this bi-directional cross-talk resulting in protection against bone damage.…”
Section: Discussionmentioning
confidence: 94%
“…MMPs play an important role in cartilage and bone destruction in arthritic joints [35,36]. These enzymes also participate in the migration of DC to the secondary lymphoid tissue and the site of inflammation [37,38].…”
Section: Pristimerin Suppresses the Activity Of Matrix Metalloproteinmentioning
confidence: 99%
“…Another physiological modulator of RANKL activity is MMP-9, which has been shown to play an important role in bone remodeling (48). For example, MMP-9 activity is involved in the promotion of RANKL-induced osteoclastogenesis independent of NFATc1 signaling (48).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MMP-9 activity is involved in the promotion of RANKL-induced osteoclastogenesis independent of NFATc1 signaling (48). Furthermore, IL-1␤ can stimulate FLS/osteoclasts and chondrocytes to produce MMPs that degrade cartilage (45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silibinin hampered osteoclastogenesis signaling by down-regulated the enzyme activity of RANKL-induced MMP-9. It is shown that MMP-9 enzyme action is engaged in the promotion of RANKL-induced osteoclastogenesis independent of NFATc1 signaling [Franco et al, 2011]. Similarly, the isoflavone genistein down-regulated RANKL production and MMP-9 activity and inhibited osteoclast formation, resulting in the inhibition of osteoclastic bone resorption and prostate cancer bone metastasis [Li et al, 2006].…”
Section: Discussionmentioning
confidence: 99%